Early Loss of Primary Molars and Changes in Body Mass Index in Students Aged 7–9 Years - Kaban, Luly Kartika Dewi Br.; Hanan, Nydia; Isnuwardana, Ronny; Munir, Musnar; Fitriany, Evi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: The early loss of primary teeth denotes the loss of teeth in the oral cavity before the typical loss timeframe. The early loss of primary molars markedly impacts masticatory function. Children of elementary school age frequently encounter dental and oral health issues. This study aims to determine the correlation between the premature loss of primary molar teeth and variations in body mass index (BMI) among 7-9-year-old students at Public Elementary School (SDN) 003 Sungai Kunjang. Material and Methods: This study employed an analytical approach with a prospective cohort design. The demographic comprises students aged 7 to 9 years at SDN 003 Sungai Kunjang, Samarinda City, with 233 respondents. Sampling was conducted via a non-probability purposive sampling method. This study utilized oral diagnostic instruments, manual scales, stadiometers, stationery, identity questions, and examination forms. Results and Discussions: Bivariate data analysis employing the chi-square test on the early loss of primary molars and alterations in student BMI indicated that respondents with early loss of primary molars were 8.824 times more likely to exhibit a reduction in BMI than those without early loss of primary molars. Conclusion: The study finds that a correlation exists between the early loss of primary molars and alterations in BMI among 7-9-year-old students at SDN 003 Sungai Kunjang